The Effect of Quercetin Supplementation on Oxidative Stress, Glycemic Control, Lipid Profile and Insulin Resistance in Type 2 Diabetes: A Randomized Clinical Trial - Zohreh Mazloom; Seyedeh Maryam Abdollahzadeh; Mohammad Hossein Dabbaghmanesh; Abbas Rezaianzadeh (Shiraz University of Medical Sciences, 2014)
Background: Diabetes Mellitus (DM) is closely associated with reduction of antioxidant defense system. In the present study, we investigated the antioxidant effect of quercetin supplementation on the glycemic control, lipid profile and oxidative stress indices in patients with type 2diabetes. Methods: Forty seven patients with type 2 diabetes, aged 30-60 years old, were randomly assigned to supplement their daily diet with either an oral quercetin (250 mg/d) or identical placebo (cellulose) capsules for 8 weeks. The supplements were provided to the patients biweekly. Anthropometric data as well as glycemic indices, lipid profile and oxidative stress parameters of blood samples were determined at the baseline and endpoint of the study. Results: Dietary quercetin supplementation significantly improved the total antioxidant capacity (TAC) in the intervention group, when compared to the placebo group (P=0.043). It also resulted in a statistically significant reduction in serum concentration of atherogenic oxidized LDL (ox-LDL) (P0.05). Conclusions: Oral quercetin supplementation was beneficial in improving the antioxidant status of patients with type 2 diabetes while having no other significant effect on glycemic control and lipid profile; however, conducting further studies, using different doses, on the glycemiccontrol and/or hyperlipidemia of thepopulation seems to be valuable. Trial Registration Number: IRCT2012101911168N